Thematic Park As Recreational Areas: Recidents Preferences - Enok Maryani; Apay Safari; Anti Riyanti; Hadi Mulyana (Universitas Pendidikan Indonesia, 2023)
The existence of city parks as Green Open Space (GOS) is very important. It has not only ecological and hidrological function, but also recreational function. It also becomes social capital developer of urban communities. This study examined the existence of GOS in Bandung, and residents’ preferences for choosing thematic parks as recreational place. The study was conducted through surveys, observation, documentation, and literature. The survey was conducted to 100 respondents in 11 thematic parks in Bandung. There were several findings of this study. First, parks in Bandung only covered 43% of the total area of Bandung. In fact, the portion of the parks should be 30% of the total region. Thus, there was a deficiency (56.73%). Second, there were several factor motivating the residents coming to the park: access, price, and its function as recreational place. Third, the characteristic of park visitors was the quite the same. There is no significant difference in the case of gender, age, education, and occupation. Then, most of the visitor coming to the park on the weekend or after working. Regarding the length of visit, they frequently spent more than 2 hours. Fourth, there was significant correlation of park physical condition, park non-physical condition, and residents’ preferences ( 0.91 and sig. at 0.001). However, there were several things that should be addressed, such as : (1) parking lots, zebra crossing, managers who monitor the park and internet facilities; and (2) limited areas for activities, seating, plant diversity, and garden lighting at night. In addition, the name of the park needs to be carefully considered to suit the purpose, location, and interests of residents.